Green Anesthesia – The Impact of Anesthetic Gases on the Environment and the Application of Alternative Methods such as TIVA, LFA, and RA - Piosik, Szymon; Olesiński, Bruno; Niemiec, Bartosz; Dudziak, Natalia; Drozd, Zuzanna; Piasecki, Łukasz; Skorupa, Aleksandra; Pawłowska, Paulina; Guzowicz, Zuzanna; Kamińska, Monika (Journal of Education, Health and Sport, 2025)
Background. Climate change and global warming pose one of the greatest threats to public health. The medical sector, responsible for a significant percentage of global greenhouse gas (GHG) emissions, faces the necessity of reducing its carbon footprint. Among the main sources of pollution in healthcare are volatile anesthetic agents, such as desflurane, sevoflurane, and isoflurane, which exhibit a high Global Warming Potential (GWP) and are released into the atmosphere in unchanged form. Aim. This systematic review aims to analyze the environmental impact of these anesthetic gases and present alternative, more sustainable anesthesia methods, including Total Intravenous Anesthesia (TIVA), Low-Flow Anesthesia (LFA), and Regional Anesthesia (RA). Material and methods. A systematic review of the scientific literature was conducted using the PubMed and Google Scholar databases. Search phrases included: green anesthesia, TIVA, low-flow anesthesia, regional anesthesia, and anesthesia environmental. After initial screening, 27 articles published since 2020 were selected for detailed analysis to serve as the basis for this systematic review. Results. The results clearly indicate that TIVA, LFA, and RA significantly reduce the carbon footprint. Furthermore, TIVA and LFA offer measurable clinical benefits, such as a reduction in postoperative cognitive dysfunction, faster recovery, and lower operational costs. The most significant environmental impact is attributed to desflurane (highest GWP), while sevoflurane is the most ecological of the inhaled agents. Conclusions. The application of alternative methods (TIVA, LFA, RA) is crucial for significantly reducing the carbon footprint associated with anesthesia, without compromising patient comfort. Key elements for implementing these changes include educating medical staff and investing in appropriate equipment to transition towards more conscious and sustainable anesthetic practices.